Successful treatment of recurrent metastatic nasopharyngeal carcinoma with nivolumab: a case report - Yu. M. Bychkov; A. M. Mudunov; I. M. Gelfand; B. G. Pkheshkhova; O. D. Ryzhova; А. A. Akhundov; V. Z. Dobrokhotova; М. N. Narimanov (Опухоли головы и шеи)
The study objective is to report a case of successful treatment of disseminated nasopharyngeal carcinoma with nivolumab.Materials and methods. A 22-year-old male patient was admitted to N.N. Blokhin National Medical Research Center of Oncology with a diagnosis of T3N3M1 stage IV nasopharyngeal carcinoma with bone metastasis. After a course of radical chemoradiotherapy, the patient was found to have cancer progression. Between September 2016 and July 2017, the patient received chemotherapy with 3 lines of drugs, but with no effect. We decided to initiate treatment with PD-1 inhibitors. The patient received nivolumab 3 mg/kg every 2 weeks between July 2017 and March 2018.Results. Positron emission tomography (September 2018) demonstrated no increased uptake of [18F]-fluorodeoxyglucose in earlier identified cancer foci. Since September 2018, the patient has been in persistent remission without any therapy.Conclusion. This case report demonstrates high efficacy of PD-1 inhibitors in the treatment of disseminated recurrent nasopharyngeal squamous cell carcinoma, resistant to standard radiotherapy and chemotherapy.